Correlation among Sterilization, Antibiotic Resistance and Malnutrition with Surgical Site Infection in a Teritary Level Hospital - Islam, Mohammad Jayedul; Suma, Sharmin Akter; Hassan, A S M Farhad Ul; Ekramul Hoque, Abu Mohammad; Daisy, Nazia Sultana; Islam, K M Shaiful; Khan, Mohammad Saifuddin (Journal of Shaheed Suhrawardy Medical College, 2023)
Background: Despite the advances made in asepsis, antimicrobial drugs, sterilization and operative techniques, surgical site infection (SSI) continues to be a major problem in all branches of surgery in the hospitals. However, there is no infection control policy that runs effectively in our country. Aim:This study was designed to see the correlation among sterilization, antibiotic resistance and malnutrition with surgical site infection in a tertiary level hospital. Methods: This cross-sectional observational study was conducted in the Department of Surgery, Shaheed Suhrawardy Medical College and Hospital. Informed written consent, detailed history, physical examination and necessary investigations were performed. Total 160 admitted patients undergoing different surgical procedure were included in this study, irrespective of their age, sex, race and ethnic group. Data were collected by using a semi-structured questionnaire. Collected data were analyzed by the SPSS 25. Results: Average age of all patient was 36.10±12.15 years (range: 13-65 years), wherein maximum patients were aged <40 years, male gender (56.3%), had normal BMI (61.3%) and non-smoker (62.07%). About 1/4th patients had diabetes mellitus. Maximum patients had undergone abdominal surgery (34.4%) followed by orthopaedic and traumatology (20.6%),General surgery other than abdominal surgery (18.8%), Neurosurgery (13.8%), Vascular surgery (12.5%). Pre-operative waiting period for surgery was <3 days in most of the cases (48.8%), followed by 3-7 days (31.3%) and >7 days (20%). Mean operation duration was 1.49±0.73 hours. Twenty-nine patients (18%) developed SSI, of which 7% had deep incisional SSI, 6% had superficial incisional SSI and 5% had organ/space SSI. SSI culture reports showed that majority (93.1%) had positive culture growth, wherein 66.7% had single microorganism and rest 33.3% had multiple growth. Staphylococcus aureus (34.48%) was the most frequently found microorganism. surgical team sterility was properly maintained in maximum surgical procedures (71.9%). Besides, OT room and surgical instruments were also properly sterilized in most of the cases (65.6% and 70%, respectively). Older age, abnormal BMI, smoking history, DM, longer pre-operative waiting period and operation duration was significantly associated with development of SSI. Besides, surgical team sterility, OT room sterility and Instrument sterility were not properly maintained in most of the surgical procedures among SSI patients (65.52%, 68.97% and 58.62%, respectively). Conclusion: Abnormal BMI (underweight and overweight or obese) and poor sterilization had significant association with development of SSI. However, further studies are needed to establish and use the findings. J Shaheed Suhrawardy Med Coll 2021; 13(2): 143-149